2020
DOI: 10.1186/s41938-020-00292-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of jatropha oil extract against the Varroa mite, Varroa destructor Anderson & Trueman (Arachnida: Acari: Varroidae), infesting honeybee colonies (Apis mellifera L.)

Abstract: The Varroa mite, Varroa destructor Anderson & Trueman (Arachnida: Acari: Varroidae), is a severe external parasitic mite of honeybees that causes great losses of colonies globally. Four concentrations (1, 2%, 5, and 10%) of Jatropha curcas oil were tested for controlling the Varroa mite. Significant effects of reducing percentage of the mite infestation (P = 0.05) after second treatment for sealed brood and after third treatment for adult workers in all tested concentrations of J. curcas were recorded. The low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…3, 4 and 5). Masry et al [50] reported a similar result when the surface of the sealed worker brood area was increased after the treatment of honey bee colonies with Jatropha curcas oil. Similarly, Stevanovic et al [51] presented the benefi cial effect of a medicinal mushroom Agaricus brasiliensis extract (sugar syrup or candy) on brood rearing improvement and adult population growth in comparison to untreated bee colonies.…”
Section: Discussionmentioning
confidence: 66%
“…3, 4 and 5). Masry et al [50] reported a similar result when the surface of the sealed worker brood area was increased after the treatment of honey bee colonies with Jatropha curcas oil. Similarly, Stevanovic et al [51] presented the benefi cial effect of a medicinal mushroom Agaricus brasiliensis extract (sugar syrup or candy) on brood rearing improvement and adult population growth in comparison to untreated bee colonies.…”
Section: Discussionmentioning
confidence: 66%
“…De igual manera, el uso de aceites esenciales como el eucalipto (Eucalyptus spp. ), el neem (Azadirachta indica) y el pomelo (Citrus maxima) reportan toxicidades superiores al 70% sobre este ácaro (Dimetry et al, 2005;Elzen et al, 2000;Melathopoulos et al, 2000). Por otra parte, Ariana et al (2002), describieron un efecto tóxico el cual oscila entre el 45 y 97% mediante el uso de aceites esenciales de Saturea hortensis L., Zataria multifera Boiss, Mentha spicata L., Rosemarinus officinalis L., Origanum vulgare L., Lavandula officinalis L. y Anethum graveolens L en contra V. destructor.…”
Section: Productos Derivados De Plantas En Contra De Varroa Destructorunclassified
“…Therefore, there is an urgent need to find eco-friendly strategies that are both affordable and safe for humans and honey bees to control Varroa mites. Numerous studies have been conducted on natural remedies, such as plant extracts and essential oils, against V. destructor in honey bee colonies [ 354 , 355 , 356 ]. The efficacy of certain plant-based essential oils, such as eucalyptus, thyme, neem, sage, and grapefruit, against Varroa mites has been reported in many studies.…”
Section: Antimicrobial Activity Of Labmentioning
confidence: 99%